"Wartości azjatyckie" jako próba stworzenia podstaw tożsamości narodów Azji Wschodniej - Drelich-Skulska, Bogusława (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
In general, "Asian values" are described as the Asian strategy of negotiations over the position in the eurocentristic views upon modernity. The negotiations emphazise a diversity of cultures, communities and development stages, especially in the case of countries of the Asia-Pacific region. Nowadays, the idea of "Asian values" is most promoted - by the academic and political elites in the countries of East Asia - as a programme aimed at the resurgence of the traditional value system -the return to the Asian roots of national identity. In the opinion of many promotors of this idea, it is a counterweight to the Western civilization as well as it is the groundwork for the creation and justification of the Asian model of economic and social development in the world. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 96-103